Effect of Ultrasonic Decrystallisation on Physicochemical Properties of Loquat Honey - XU Sijia, LUO Shiye, WANG Zhaoli, HE Juan, LUO Chunliang, LI Xiangxin, PENG Wenjun, FANG Xiaoming (Shipin Kexue, 2025)
In this study, the effect of ultrasonic on the decrystallisation rate and physicochemical properties (crystal microstructure, rheological properties, textural properties, color, enzyme activities, total phenols, total flavonoids, 5-hydroxymethylfurfural, antioxidant and antibacterial capacity) of loquat honey was investigated, and the action mechanism was revealed using an online real-time temperature monitoring system. The results showed that ultrasonic cavitation and thermal effects worked together to decompose the cluster crystal structure in loquat honey. After 80 min of ultrasonic decrystallisation at 400 W and 40 kHz, the temperature of loquat honey increased to 55.9 ℃, and the decrystallisation rate reached up to (98.2 ± 0.65)%. In addition, ultrasonic decrystallisation effectively changed loquat honey from a pseudoplastic fluid into a Newtonian fluid, leading to a decrease in hardness and gumminess and an increase in chewiness. Furthermore, ultrasonic decrystallisation facilitated the release of total phenols and flavonoids in loquat honey, thereby enhancing its antioxidant activity. However, the thermal effect and free radicals generated by ultrasonic treatment resulted in the accumulation of 5-hydroxymethylfurfural (5-HMF) and the consumption of reducing sugar by accelerating the Maillard reaction, and led to a decrease in the antibacterial capacity by inhibiting the glucose oxidase activity of loquat honey. The objective of this study is to provide a feasible non-thermal decrystallisation method for honey and technical guidance for promoting the industrial application of efficient decrystallisation technology.